My beloved man the letters of Benjamin Britten and Peter Pears - Britten, Benjamin 1913-1976; Pears, Peter 1910-1986 (The Boydell Press, 2016)
This volume comprises the complete surviving correspondence between Benjamin Britten and Peter Pears. The 365 letters written throughout their 39-year relationship are here brought together and published, as Pears intended, for the first time. While the correspondence provides valuable evidence of the development of Britten's works, more significant is theinsight into his relationship with Pears and their day-to-day life together. Entertaining to read, domestic and intimate, the letters provide glimpses of cultural and artistic life in the twentieth century, including pacifism and conscientious objection, critical assessments of music and other artists, transport and communications development in the twentieth century, the 'Aldeburgh corpses', artcollecting, gossip, everyday life in an English country house, the development of the Aldeburgh Festival, performance practice in early music, looking after dachshunds, travel, and a host of other topics. Above all, when read together, Britten and Pears's letters allow the clearest possible look 'behind the scenes' of one of the most productive creative partnerships of the twentieth century. - VICKI P. STROEHER is Professor of Music History at Marshall University where she is also Coordinator of the Music History & Literature area. NICHOLAS CLARK is the Librarian at the Britten-Pears Foundation at The Red House, Britten and Pears's home in Aldeburgh, Suffolk. JUDE BRIMMER is an Archivist at the Britten-Pears Foundation. (Klappentext)
Foreword by Fiona Shaw
Keywords: Britten, Benjamin -- 1913-1976; Pears, Peter -- 1910-1986; Geschichte 1937-1976; Briefsammlung